2013
DOI: 10.1017/s0007114513000068
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Tuscan black cabbage sprout extract against serum lipid increase and perturbations of liver antioxidant and detoxifying enzymes in rats fed a high-fat diet

Abstract: A diet rich in fat is considered a primary risk factor for CVD, cancer and failures in metabolism and endocrine functions. Hyperlipidaemia generates oxidative stress and weakens antioxidant defences as well as metabolic detoxification systems. Brassicaceae are vegetables rich in glucosinolates and isothiocyanates, affecting enzymatic antioxidant as well as phase II enzymes and conceivably counteracting high-fat diet (HFD)-associated pathologies. The protective role of Tuscan black cabbage (a variety of kale) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…It is worth noting that, TBK-SE was free of the goitrogenic progoitrin ((2 S )-2-hydroxy-3-butenyl GL) and contained only limited amount of indole GLs, 0.98 % (w/w) 4-hydroxy-glucobrassicin (4-OH-GBS, 4-hydroxy-3-indolylmethyl GL), 0.18 % (w/w) glucobrassicin (GBS, 3-indolylmethyl GL), 0.21 % (w/w) 4-methoxy glucobrassicin (4-OMe-GBS, 4-methoxy-3-indolylmethyl GL) and 0.67 % (w/w) neoglucobrassicin (Neo-GBS, N-methoxy-3-indolylmethyl). Treatment of TBK-SE with Myr enzyme catalyzed the quantitative transformation of aliphatic GLs into ITCs, R -sulforaphane being the major one, as already described [ 20 ], thus indole GLs are known to be hydrolysed into highly unstable ITC and are spontaneously transformed to carbinols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that, TBK-SE was free of the goitrogenic progoitrin ((2 S )-2-hydroxy-3-butenyl GL) and contained only limited amount of indole GLs, 0.98 % (w/w) 4-hydroxy-glucobrassicin (4-OH-GBS, 4-hydroxy-3-indolylmethyl GL), 0.18 % (w/w) glucobrassicin (GBS, 3-indolylmethyl GL), 0.21 % (w/w) 4-methoxy glucobrassicin (4-OMe-GBS, 4-methoxy-3-indolylmethyl GL) and 0.67 % (w/w) neoglucobrassicin (Neo-GBS, N-methoxy-3-indolylmethyl). Treatment of TBK-SE with Myr enzyme catalyzed the quantitative transformation of aliphatic GLs into ITCs, R -sulforaphane being the major one, as already described [ 20 ], thus indole GLs are known to be hydrolysed into highly unstable ITC and are spontaneously transformed to carbinols.…”
Section: Resultsmentioning
confidence: 99%
“…TBK-SE was analysed for GL profile and content according to the EU official ISO 9167–1 method [ 19 ] which is based on the HPLC analysis of desulfo-GL, as previously described [ 20 ]. Eight independent HPLC determinations were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Catalase (CAT) activity was measured by the amount of hydrogen peroxide (H 2 O 2 ), which is produced by CAT. The decomposition of the substrate was measured using a spectrophotometer at 240 nm, and one unit activity was expressed as moles of H 2 O 2 consumed per minute per mg protein [20]. The lipid peroxidation concentration in the microsomes was assessed by measuring thiobarbituric acid (TBA) substances [21].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Bacchetti et al (2014) found that supplementation with brassica influenced on serum lipid profile with a significant decrease in total cholesterol, LDL-cholesterol and oxidized LDL. In addition brassica vegetables have been shown to exert a protective effect against many chronic degenerative diseases, including cancer (Herr & Buchler, 2010;Manchali, Murthy, & Patil, 2012;Melega et al, 2013).…”
Section: Vegetablesmentioning
confidence: 99%